Mechanical characteristics analysis of horizontal lifting of subsea pipeline with different burial depths - Zhang, Dapeng; Zhao, Bowen; Zhu, Keqiang (Frontiers in Earth Science, 2022)
With the consideration of the soil resistance to subsea pipelines, combined with the specific sea condition parameters of a certain sea area, and based on the lumped mass method, the subsea pipeline is discretized into a lumped mass model, the dynamic analysis model of three-point horizontal lifting of subsea pipelines with different burial depths is established, the stress and bending of the pipelines with different burial depths are analyzed, and the calculation results with different burial depths are compared and analyzed. The variation of mechanical characteristics of the process of lifting horizontal pipelines with different buried depths is obtained. The results show that the change of burial depth has a significant influence on the effective tension of the pipeline. With the increase of the burial depth, the maximum degree of stretching of the pipeline first decreases and then increases. Within a certain depth range, burying the pipeline in the seabed can reduce both the effective tension and the intensity of the fluctuation of the effective tension when the pipeline is lifted. The change of burial depth for the change of shear action is mainly reflected in the change of the numerical value of the shear force, and has no significant impact on the degree and variation fluctuation of the shear force. The conclusions can provide certain theoretical reference for the design of the process of the horizontal pipeline lifting.